1997
DOI: 10.1152/ajpendo.1997.273.3.e536
|View full text |Cite
|
Sign up to set email alerts
|

Roles of intensity and duration of nocturnal exercise in causing phase delays of human circadian rhythms.

Abstract: To determine the roles of intensity and duration of nocturnal physical activity in causing rapid phase shifts of human circadian rhythms, eight healthy men were studied three times under constant conditions with no exercise, a 3-h bout of moderate-intensity exercise, or a 1-h bout of high-intensity exercise. Exercise stimulus was centered at 0100. Circadian phase was estimated from the onsets of the nocturnal elevation of plasma thyrotropin (TSH) and melatonin. Mean phase shifts of TSH onsets were -18 +/- 8 (b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
141
5
6

Year Published

2001
2001
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(165 citation statements)
references
References 15 publications
13
141
5
6
Order By: Relevance
“…The results of these early studies were confounded by the limitations of the circadian phase measures used and the conditions under which circadian phase was estimated. More recent studies involving exposure to a single stimulus over a background of constant conditions demonstrated that exposure of humans to nocturnal exercise results in significant phase delays of circadian hormonal rhythms (8,24,30). Consistent with the phase-delaying effects of exposure to single bouts of nocturnal exercise, a field study examining the entrainment of night workers to a daytime sleep schedule found that subjects exposed to nocturnal exercise experienced phase delays in the rhythm of body temperature greater than those observed in a control group not exposed to exercise, although statistical significance was only achieved if the morningnesseveningness of the control group was taken into account (15).…”
mentioning
confidence: 99%
“…The results of these early studies were confounded by the limitations of the circadian phase measures used and the conditions under which circadian phase was estimated. More recent studies involving exposure to a single stimulus over a background of constant conditions demonstrated that exposure of humans to nocturnal exercise results in significant phase delays of circadian hormonal rhythms (8,24,30). Consistent with the phase-delaying effects of exposure to single bouts of nocturnal exercise, a field study examining the entrainment of night workers to a daytime sleep schedule found that subjects exposed to nocturnal exercise experienced phase delays in the rhythm of body temperature greater than those observed in a control group not exposed to exercise, although statistical significance was only achieved if the morningnesseveningness of the control group was taken into account (15).…”
mentioning
confidence: 99%
“…This is a significant report lending support to the results we obtained with daytime exercise. In a study by Buxton et al 16 8 healthy individuals were subjected to 3 hours of moderate exercise and 1 hour of high-intensity exercise to find out the effects of the duration and intensity of nocturnal physical activity on human circadian rhythms. It was concluded that nighttime physical activity impaired the human circadian rhythm.…”
Section: Discussionmentioning
confidence: 99%
“…There is massive evidence that PE may act as a non-photic synchronizer, being able to dislocate the circadian rhythms phase (17)(18)(19)(20)(21)(22)(23)(24) . This phenomenon may be observed when PE is applied in constant situations, in which the influence of other synchronizers both photic and non-photic are tried to be blocked.…”
Section: Physical Exercise As a Non-photic Synchronizermentioning
confidence: 99%
“…The longest phase delays could be observed when the stimulus was presented three to five hours before the temperature nadir. Buxton et al (1997) (22) investigated the role of the intensity and duration of nocturnal PE in the modification of the thyreotropin and melatonin rhythms expression. The authors studied a group of 8 male healthy adult subjects (20-30 years), who received two pulses of PE at one o'clock in the morning at different days.…”
Section: Physical Exercise As a Non-photic Synchronizermentioning
confidence: 99%
See 1 more Smart Citation